Among-Based Peer Counseling for Bullying Prevention: An SDGs-Oriented Approach to Safe and Inclusive Education - Miranti; Iskandar; Edi Saputra; Mahmoud Abderaman Hassane (Universitas Muhammadiyah Surakarta, 2026)
Objective: This study aims to analyze the effectiveness of Among value-based peer counseling in reducing bullying, as well as identifying supporting and inhibiting factors for its implementation in the school environment. Theoretical framework: The theoretical framework refers to the educational concept of Among Ki Hadjar Dewantara (Ing Ngarso Sung Tulodho, Ing Madyo Mangun Karso, Tut Wuri Handayani), which is combined with the peer counseling approach and social interaction theory. Literature review: The literature emphasizes the effectiveness of peer counseling in reducing bullying and the importance of integrating local wisdom values in building students' empathy, character, and social relations. Methods: Using a qualitative approach with a case study design, through interviews, participatory observations, documentation, and questionnaires, as well as thematic data analysis. Results: The results of the study showed a significant decrease in verbal and relational bullying, an increase in students' empathy and social awareness, a strengthening of the role of peer counselors as agents of change, the internalization of Among values in school culture, structural and cultural support as success factors, and the existence of personal and technical constraints that affect the sustainability of the program. Implications: Contribute to the development of a humanistic, contextual, and sustainable counseling model based on local wisdom. Novelty: Lies in the integration of Among values in peer counseling as an innovative approach that not only suppresses bullying but also forms a positive school culture.